One-step manufacturing process for neodymium-iron (magnet-grade) master alloy - Prabhat K. Tripathy (KeAi Communications Co., Ltd., 2021)
Neodymium iron boron magnet has registered heightened demand due to its rapidly increasingly application in the clean energy sector. These magnets are manufactured by melting the mixture, consisting of neodymium, iron and boron followed by casting into ingots. The ingots are subsequently pulverized to powder, which, in turn, is sintered and magnetized to form the permanent magnet. An alternative approach is the controlled addition of boron to the neodymium iron master alloy to fabricate the magnet. The present process discusses an alternative and novel electrochemical approach to prepare the neodymium-iron master alloy, directly from the mixed oxides of neodymium and iron, in just one step. The mixed oxide pellet was cathodically polarized in a pool of molten calcium chloride in the temperature range 800–950°C, against an oxygen-evolving anode. The reduced alloy could not only retain its original structure but also exhibited magnetic behavior.